Estudo institucional e apreciativo do atual estágio de institucionalização da Secretaria da Controladoria-Geral do Estado de Pernambuco - SANTOS, Thiago Antonio Cavalcanti Bizinco dos (2023)
This dissertation aims to develop a study that can highlight the role of actors ahead of the institutional work and the appreciative perspective applied to the case of the Secretariat of the Controller General of Pernambuco (SCGE/PE) in terms of its stage of institutionalization, internal control agent and accountability. The theoretical foundation comprised the themes of Controllership, Internal Control in Public Management, Accountability, Institutional Theory, Institutional Work and Appreciative Inquiry (AI). The research is qualitative, descriptive-exploratory, and documentary in nature. A case study was carried out involving procedures associated with the initial 4-Ds of the 5-D model of AI: 1-D Definition, 2-D Discovery, 3-D Dream, 4-D Design, and 5-D Destiny, which are also thematic descriptors of the analysis, associated with the institutional elements used. To this end, a collaborative group was set up, as a representative actor of SCGE/PE, composed of six members of the institution (representing the strategic, tactical and operational levels) who actively participated in the process of data collection, analysis and validation carried out by means of workshops, with the use of remote resources. The results indicated that there are predominant patterns of objectification and initial characteristics of the sedimentation underway in the institutionalization process of SCGE/PE, which is expressed as a positive institution of internal control and accountability, acting mainly as a strategic and support core for the state public administration and for society. The presence of the three types of institutional work (political, technical and cultural-cognitive) was also evidenced through the actions undertaken by its actors, in a combined and mutually articulated manner to ensure the institutionalization process as it has been conducted and to generate possibilities to be explored in relation to the Comptroller's vision for the future. In this particular, it was noted that efforts should be undertaken aiming at the improvement, institutional consolidation and legitimization of SCGE/PE. Finally, the results obtained suggest the continuity of studies on this theme and open space for new research, including that involving SCGE/PE, whose institutional trajectory is in an active process of construction and development.